Kinerja Saham dalam Konteks Determinan Pasar Keuangan di Perusahaan Energi - Reydatus Rafiawan Akbar; Nera Marinda Machdar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the effect of market risk, investor sentiment, and interest rates on the performance of energy sector stocks in Indonesia for the period 2019–2023, with market liquidity as a mediating variable. The study was conducted through a literature review by identifying and analyzing various related studies. Secondary data was obtained from scientific journals and related reports using relevant literature selection techniques. The results of the study indicate that oil price volatility, investor sentiment, and interest rate changes significantly affect the performance of energy sector stocks. Market liquidity was found to be able to reduce the negative impact of market risk and interest rates, and strengthen the positive influence of investor sentiment on stock prices. This study concludes that market liquidity plays an important buffer in maintaining the stability of stocks in the energy sector, especially in dealing with market fluctuations. The results of this study contribute to investment managers in developing more adaptive portfolio strategies and to regulators in creating policies that support market liquidity.